Planning of Optimal Raw Materials Inventory Using the Marcov Chain Method - Rina Handayani; Manaek Hamonangan Sihombing (Journal of Science Technology (JoSTec), 2022)
Inventory is an important issue to control. Both finished goods and raw material inventories are the same with ingredient raw for the production process . no seldom our find problem where company no To do good control _ in management inventory that results in needs customer no fulfilled . Ray Traso Jaya is company that manufactures and sells paving block products , bataco , riol concrete and pits wind where in the production process experience disturbance in carry out the production process caused level management supply ingredient raw sand and cement that are not optimal as a result company difficulty for Fulfill needs customers who are fluctuating . Formulas problem in study this is " How " determine supply ingredient raw materials and costs supply ingredient optimal raw material at Sinar Traso Jaya?”. Study this aim for determine supply ingredient optimal raw material and cost supply ingredient optimal raw . Method analysis used _ in research this is method Analysis Calculation With Markov Chain. Where is the result study this company can adapt costs required at the time level booking with ingredient fluctuating standard _ with notice stock ingredient available raw . _ That is if ingredient raw sand initial 0 or stock empty on level ordering 170.638 kg the optimal cost is at Rp. 1300,000 , if ingredient cement raw 0 or stock empty on level booking as much as 57,617 kg with the optimal cost is IDR 1,300,000.